Phosphorous adsorption on synthesized magnetite in wastewater - Choi, Jeongyun; Chung, Jinwook; Lee, Wonhee; Kim, Jong-Oh (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
•Phosphate in water was recovered completely by dry-form magnetic iron oxide (MIO).•Elovich model reasonably simulated the behavior of phosphate adsorption on MIO.•Freundlich model was fitted well for describing the phosphate isotherm on MIO.•Phosphate-sdsorbed MIO can be effectively regenerated with dilute NaOH solution. The phosphorous adsorption on a synthesized magnetic iron oxide (MIO) was conducted using a batch type experiment. A dry-form MIO was used in adsorption experiment to obtain useful information for practical application. The Elovich model reasonably simulated the two-step adsorption process in the kinetic experiments. Freundlich isotherm model was better than the Langmuir model for describing the phosphate isotherm on MIO. The maximum adsorption capacity of MIO was 15.2mgP/g MIO which was achieved at the pH less than 5. The adsorbed phosphorous was effectively detached from MIO within 30min using 20wt% NaOH solution.